2008
DOI: 10.1029/2008jg000781
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing data assimilation for a prognostic phenology model

Abstract: [1] Predicting the global carbon and water cycle requires a realistic representation of vegetation phenology in climate models. However most prognostic phenology models are not yet suited for global applications, and diagnostic satellite data can be uncertain and lack predictive power. We present a framework for data assimilation of Fraction of Photosynthetically Active Radiation absorbed by vegetation (FPAR) and Leaf Area Index (LAI) from the MODerate Resolution Imaging Spectroradiometer (MODIS) to constrain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 109 publications
2
114
0
1
Order By: Relevance
“…In turn, these seasonal changes are largely regulated by climatic conditions and in particular by three main factors: temperature, photoperiod and moisture availability (Jolly et al 2005). These climatic factors impose spatially and temporally variable constraints on vegetation activity (Körner and Basler 2010), which may be modelled at various scales (Stöckli et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these seasonal changes are largely regulated by climatic conditions and in particular by three main factors: temperature, photoperiod and moisture availability (Jolly et al 2005). These climatic factors impose spatially and temporally variable constraints on vegetation activity (Körner and Basler 2010), which may be modelled at various scales (Stöckli et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some vegetation models, developers went beyond just dates and linked seasonal dynamics of leaf area index (LAI) to thermal time based on plant thermal response functions (Neitsch et al, 2002;Bondeau et al, 2007;Rötzer et al, 2010). In other works researchers started using multiple factors simultaneously to derive phenological trajectories (Jolly et al, 2005;Setiyono et al, 2007;Stöckli et al, 2008). Finally, the interactive approach has been extended to include the concept of event drivers with the first successful trials reported in the companion paper (Kovalskyy and Henebry, 2011).…”
Section: Kovalskyy and G M Henebry: The Event Driven Phenology Mmentioning
confidence: 99%
“…Land surface phenology studies the spatiotemporal development of the vegetated land surface using remote sensing (de Beurs and Henebry, 2004), and sometimes called "remote sensing phenology" (Morisette et al, 2009). Several pioneering studies in land surface phenology (de Beurs and Henebry, 2004;Reed, 2006;Zhang et al, 2007;Stöckli et al, 2008;Xiao et al, 2009) point to the need to move beyond the conventional representation of LSPs as static trajectories of vegetation cover properties with negligible response to changing weather conditions.…”
Section: Kovalskyy and G M Henebry: The Event Driven Phenology Mmentioning
confidence: 99%
“…5), and their influence on crop establishment and growth are still rather poorly represented within SPAc. RS DA is also a suitable tool for mitigating uncertainties due to model parameters and weak understanding of phenological processes (Stöckli et al, 2008). There is clear value in making use of MODIS' full spatiotemporal richness when addressing current key uncertainties of upscaled crop modelling.…”
Section: Model Improvement Through Sequential Modis Damentioning
confidence: 99%
“…Bondeau et al, 2007;de Noblet-Ducoudré et al, 2004;Kucharik and Twine, 2007;Sus et al, 2010), which traditionally lacked a crop-specific plant functional type. Generally, BGCMs would benefit from a better representation of interannual phenological variability, which is poorly understood (Richardson et al, 2012;Stöckli et al, 2008).…”
mentioning
confidence: 99%